Paeoniflorin Alleviates Abnormalities in Rats with Functional Dyspepsia by Stimulating the Release of Acetylcholine - Zou X; Wang Y; Wang Y; Yang J; Guo H; Cai Z (Dove Medical Press, 2020)
Xuan Zou,1,2,* Yang Wang,1,2,* Yuheng Wang,3 Junting Yang,3 Huishu Guo,1,2 Zhengxu Cai3 1Central Laboratory, The First Affiliated Hospital of Dalian Medical University, Dalian 116001, People’s Republic of China; 2Institute (College) Integrative Medicine, Dalian Medical University, Dalian 116044, People’s Republic of China; 3Department of Neurology, The First Affiliated Hospital of Dalian Medical University, Dalian 116001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhengxu CaiDepartment of Neurology, The First Affiliated Hospital of Dalian Medical University, 222 Zhongshan Road, Dalian 116001, People’s Republic of ChinaEmail caizhengxu999@126.comHuishu GuoCentral Laboratory, The First Affiliated Hospital of Dalian Medical University, 222 Zhongshan Road, Dalian 116001, People’s Republic of ChinaTel +86-411-83635963 ext 7255Email guohuishu1@126.comIntroduction: Paeoniflorin is a main active component in traditional Chinese medicine. Paeoniae alba radix is widely used as a spasmolytic and pain-relieving agent for abdominal spasmodic pain. Functional dyspepsia (FD) is characterized by pain or burning in the epigastrium, fullness, bloating and nausea. However, limited information is available about the effect of paeoniflorin on FD.Materials and Methods: In this study, iodoacetamide or clonidine-induced FD rat models were established to investigate the impacts of paeoniflorin on FD induced by different pathophysiologic disturbances.Results: We found the therapeutic effect of paeoniflorin through assessing the gastric emptying, gastric accommodation and visceral hypersensitivity. This function of paeoniflorin was related to the release of acetylcholine (ACh), which was accompanied by reduced acetylcholinesterase (AchE) activity in stomach and hypothalamus. Paeoniflorin administration inhibited the cyclo-oxygenase-2 (COX-2) expression and increased the level of ghrelin in the stomach. Besides, the levels of occludin and ZO-1 were elevated in the duodenum from paeoniflorin-treated rats, suggesting the impaired duodenal barrier was ameliorated.Discussion: These results indicate that paeoniflorin possesses the ability to alleviate functional dyspepsia.Keywords: paeoniflorin, functional dyspepsia, acetylcholine, gastric function